2022
DOI: 10.1088/1475-7516/2022/04/044
|View full text |Cite
|
Sign up to set email alerts
|

A measurement of the scale of homogeneity in the early Universe

Abstract: We present the first measurement of the homogeneity index, ℋ, a fractal or Hausdorff dimension of the early Universe from the Planck CMB temperature variations δT in the sky. This characterization of the isotropy scale is model-free and purely geometrical, independent of the amplitude of δT. We find evidence of homogeneity (ℋ = 0) for scales larger than θℋ = 65.9 ± 9.2 deg on the CMB sky. This finding is at odds with the ΛCDM prediction, which assumes a scale invariant infinite universe. Such anomaly is co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
2
8
1
Order By: Relevance
“…The main differences with Inflation is the origin of those perturbations and the existence of a cutoff in the spectrum of fluctuations given by R(τ). As illustrated in Figure 6-7, such cutoff has recently been measured in the CMB maps [9,12]. Current and future galaxy surveys are also able to measure this signal [39,105] which could also appear as a dipole [106].…”
Section: Discusion and Conclusionmentioning
confidence: 81%
See 3 more Smart Citations
“…The main differences with Inflation is the origin of those perturbations and the existence of a cutoff in the spectrum of fluctuations given by R(τ). As illustrated in Figure 6-7, such cutoff has recently been measured in the CMB maps [9,12]. Current and future galaxy surveys are also able to measure this signal [39,105] which could also appear as a dipole [106].…”
Section: Discusion and Conclusionmentioning
confidence: 81%
“…These are independent because only the former depends on the measured values of H 0 in each horizon. A recent study of the homogeneity index in the CMB [12] finds a cutoff scale Θ H = 66 ± 9 degrees. This is shown as the black symbol in Figure 7 for the mean values of Ω m = 0.3 and H 0 = 67 Km/s/Mpc in the full CMB sky.…”
Section: The Horizon Problemmentioning
confidence: 97%
See 2 more Smart Citations
“…Such a test was originally proposed by [52], and performed by [53][54][55][56] using observational data from the 2MASS photo-z catalogue, SDSS-III DR12 LRGs, SDSS blue galaxies, and Planck's CMB temperature anisotropy maps, respectively. The first works showed that the angular homogeneity scale measurements are in good agreement with the standard model expectations, albeit the concordance was weaker in [56]. In addition, our analysis probes higher redshift ranges than previous galaxy-based works, since the latest SDSS LRG dataset is composed of objects in the 0.6 < z < 1.0 interval.…”
Section: Introductionmentioning
confidence: 99%